PERANAN KELOMPOK STUDI DAN PENGEMBANGAN PRAKARSA MASYARAKAT DALAM MENINGKATKAN KEMANDIRIAN MASYARAKAT MELALUI CREDIT UNION HARAPAN MAJU DI DESA LINTONGNIHUTA, KECAMATAN RONGGURNIHUTA, KABUPATEN SAMOSIR - Johenro Silalahi (Welfare StatE, 2013)
Basically, education is expected to be able to improve standard of living. As the foundation of progress and civilization of the nation, education is required to humanize human being. Yet, in fact, formal education in Indonesia still does not pay much attention to marginal community such as farmers. Therefore, non-formal education becomes alternative. KSPPM (Study Group and Community Initiative Development) uses the strategy of the Credit Union (CU) as one of the alternative offers is expected to be the way in coping with the various limitations. This purpose of this study aims to look at how the Samosir regional plays its role in improving community self-reliance through Harapan Maju Credit Union in Lintongnihuta village. Through this descripive qualitative analytical study, the aim of this study was to describe how to improve the self-reliance of the farmers who belong to the Harapan Maju Credit Unionunder auspices of Samosir regional KSPPM. The respondents for this study were 96 active members of Harapan Maju Credit Union in Lintongnihuta Village, Ronggurnihuta Subdistrict, Samosir District. The data used for this study were those obtained through both library and field research. The result of data analysis showed that Samosir regional KSPPM played an active role in assisting the members of Harapan Maju Credit Union in improving their self-reliance. It can be seen through the fact that the farmers belonging to Harapan Maju Credit Union in Lintongnihuta Village, Ronggurnihuta Subdistrict, Samosir District are competent and reliable. Yet, some of the community members admit that the active role of Samosir regional KSPPM is not counterbalanced by strong determination to develop paradigm. Hence, improvement of several aspects must be done so that self-reliance of farming communities can be materialized. Keywords: Roles, Community, Agricultural Capital, Paradigm of Thinking